Creating, Sustaining, and Enhancing Purposeful School-University Partnerships Building Connections Across Diverse Educational Systems - Green, Corinne A.; Eady, Michelle J. (Springer Nature Singapore : Imprint: Springer, 2024)
XIII, 447 p. 20 illus., 13 illus. in color.